A prospective study of the effects of breastfeeding and FADS2 polymorphisms on cognition and hyperactivity/attention problems12. Issue 5 (4th June 2013) - Groen‐Blokhuis, Maria M.; Franić, S.; van Beijsterveldt, Catharina E.M.; de Geus, Eco; Bartels, Meike; Davies, Gareth E.; Ehli, Erik A.; Xiao, Xiangjun; Scheet, Paul A.; Althoff, Robert; Hudziak, James J.; Middeldorp, Christel M.; et al.
Abstract Breastfeeding has been associated with improved cognitive functioning. There is a beneficial effect on IQ, and possibly on associated phenotypes such as attention problems. It has been suggested that the effect on IQ is moderated by polymorphisms in the FADS2 gene, which is involved in fatty acid metabolism. In this study we tested the relation between breastfeeding and FADS2 polymorphisms on the one hand and IQ, educational attainment, overactivity, and attention problems on the other hand. IQ at age 5, 7, 10, 12, and/or 18 (n = 1, 313), educational attainment at age 12 (n = 1, 857), overactive behavior at age 3 (n = 2, 560), and attention problems assessed at age 7, 10, and 12 years (n = 2, 479, n = 2, 423, n = 2, 226) were predicted by breastfeeding and two SNPs in FADS2 (rs174575 and rs1535). Analyses were performed using structural equation modeling. After correction for maternal education, a main effect of breastfeeding was found for educational attainment at age 12 and overactive behavior at age 3. For IQ, the effect of breastfeeding across age was marginally significant (P = 0.05) and amounted to 1.6 points after correcting for maternal education. Neither a main effect of the FADS2 polymorphisms nor an interaction with breastfeeding was detected for any of the phenotypes. This developmentally informed study confirms that breastfeeding is associated with higher educational attainment at age 12, less overactive behavior at age 3 and a trend toward higher IQ after correction for maternal education. In general, the benefits of breastfeeding were small and did not interact with SNPs in FADS2. © 2013 Wiley Periodicals, Inc.